2017
DOI: 10.1007/s10120-017-0744-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nutritional Status (CONUT) score is a prognostic marker for gastric cancer patients after curative resection

Abstract: CONUT is useful for not only estimating nutritional status but also for predicting long-term OS in gastric cancer patients after curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
215
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 252 publications
(227 citation statements)
references
References 28 publications
7
215
3
2
Order By: Relevance
“…The CONUT score not only reflects the nutritional status of patients with GC but also predicts long‐term OS after surgery for GC 8. Takagi et al19 suggested that the CONUT score was a reliable predictor of long‐term prognosis after hepatectomy for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The CONUT score not only reflects the nutritional status of patients with GC but also predicts long‐term OS after surgery for GC 8. Takagi et al19 suggested that the CONUT score was a reliable predictor of long‐term prognosis after hepatectomy for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al19 suggested that the CONUT score was a reliable predictor of long‐term prognosis after hepatectomy for hepatocellular carcinoma. In addition, the predictive ability of the CONUT score is better than that of classic indicators, such as the neutrophil to lymphocyte ratio (NLR), prognostic nutritional index (PNI), and modified Glasgow Prognostic Score (mGPS) 8, 19. However, whether the predictive power of the CONUT score is superior to that of sarcopenia has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations